Chemical constituents and biological activities of Glycosmis chlorosperma var. Elmeri (Merr.) stone (Rutaceae) - Abdullah, Rosmiati; Rahmani, Mawardi; Ali, Abdul Manaf; Ismail, H.B.M.; Sukari, Mohd Aspollah; Lian, Gwendoline Ee Cheng (Faculty of Science, University of Malaya, 2006)
Detailed investigation on the leaves and barks of Glycosmis chlorosperma has led to the isolation and identification of a chalcone, dihydroglychalcone (1) and three sulphones - dambullin (2), sakambullin (3) and methylgerambullin (4), along with the common triterpene, stigmasterol. Compounds (1) (2) and (3) showed cytotoxic activity towards CEM-SS T-lymphoblastic cell lines. However, only dambullin (2) showed activity against pathogenic bacteria and fungi. We wish to report the isolation and bioassay results of the crude extracts and pure compounds.